2013
DOI: 10.1103/physrevb.88.155137
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-pressure phase diagram of CeCoSi: Pressure-induced high-temperature phase

Abstract: We have studied the temperature-pressure phase diagram of CeCoSi by electrical-resistivity experiments under pressure. Our measurements revealed a very unusual phase diagram. While at low pressures no dramatic changes and only a slight shift of the Neel temperature T-N (approximate to 10 K) are observed, at about 1.45 GPa a sharp and large anomaly, indicative of the opening of a spin-density wave gap, appears at a comparatively high temperature T-S approximate to 38 K. With further increasing pressure, T-S shi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 17 publications
5
39
1
Order By: Relevance
“…Beyond a critical point, the formation of a quasiquartet enhances the exchange interaction between Ce-planes with the consequent growth of the ordering temperature. Similar behavior was recently observed in CeCoSi under pressure showing a high temperature magnetic order also attributed to a quasiquartet level formation [19]. This facts are ascribed into a scenario of a change in the magnetic dimensionality from 2D type to 3D and the appearance of spin density waves with incommensurate wave vector.…”
Section: Discussionsupporting
confidence: 84%
“…Beyond a critical point, the formation of a quasiquartet enhances the exchange interaction between Ce-planes with the consequent growth of the ordering temperature. Similar behavior was recently observed in CeCoSi under pressure showing a high temperature magnetic order also attributed to a quasiquartet level formation [19]. This facts are ascribed into a scenario of a change in the magnetic dimensionality from 2D type to 3D and the appearance of spin density waves with incommensurate wave vector.…”
Section: Discussionsupporting
confidence: 84%
“…While changing temperature and pressure, CeCoSi undergoes two phase transitions: the antiferromagnetic (AFM) order at T N = 8.8 K at ambient pressure 24,25) and the hidden order, the latter of which dominantly appears under pressure. [26][27][28] Recently, the experiment implies that the hidden order under pressure corresponds to the antiferroquadrupole (AFQ) order, 27, 28) since it shows similar behavior to the AFQ phase observed in CeB 6 and CeTe. [29][30][31][32][33][34][35] Interestingly, the unit of the staggered AFM and AFQ orders in CeCoSi accompanies the cluster-type odd-parity multipoles, as the staggered alignment of the even-parity multipoles at two Ce sites breaks the global inversion symmetry.…”
mentioning
confidence: 99%
“…2(b), where data are partly cited in refs. [9] and [10]. In CeCoSi, there are two phase transitions at zero magnetic field: T 0 ∼ 12 K from the paramagnetic state (phase I) to the possible multipole ordered state (phase II), and T N = 9.4 K for the AFM ordered state (phase III).…”
Section: Methodsmentioning
confidence: 99%
“…CeCoSi and related materials have been studied for hydrogen storage property [7], and a catalyst for ammonia synthesis [8]. At low temperatures, an antiferromagnetic (AFM) ordering of Ce-4 f electrons takes place at T N ∼ 9.5 K [9]. Lengyel et al examined pressure effects on CeCoSi, and reported a unique pressure−temperature (P − T ) phase diagram.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation